2015
DOI: 10.1093/jat/bkv123
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Sampling Procedure on Codeine Concentrations in Oral Fluid

Abstract: For many drugs, there is a poor correlation between the plasma and oral fluid (OF) concentrations, due to differences in OF pH, oral contamination, stimulation of OF flow and variability of the volume of sample taken. The aim of this study was to evaluate the OF/plasma ratio and variability in drug concentration in OF sampled by two commercially available collection systems: Saliva Collection System (SCS) and Quantisal. Blood and OF samples were collected from 12 volunteers after intake of 19.5 mg codeine phos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 10 publications
0
5
0
Order By: Relevance
“…The OF/plasma ratio of codeine was investigated in one study and it was found that the ratio depends on which OF collection kit is used. The correlation coefficient between OF and plasma codeine concentrations was statistically significantly (p=0.005) higher for the Saliva Collection System (R 2 =0.745) than for Quantisal (R 2 =0.403) (176). Quite constant OF/blood (serum) concentrations have been found for theophylline (177) and diazepam (178).…”
Section: Oral Fluid 15mentioning
confidence: 91%
“…The OF/plasma ratio of codeine was investigated in one study and it was found that the ratio depends on which OF collection kit is used. The correlation coefficient between OF and plasma codeine concentrations was statistically significantly (p=0.005) higher for the Saliva Collection System (R 2 =0.745) than for Quantisal (R 2 =0.403) (176). Quite constant OF/blood (serum) concentrations have been found for theophylline (177) and diazepam (178).…”
Section: Oral Fluid 15mentioning
confidence: 91%
“…When oral fluid samples are adulterated, for as by sucking on the pad or placing water in the mouth, an unexplained deviation in the oral fluid samples collected can occur. Only 3.5% of the 86 oral fluid samples were found to be outside our predefined gravimetrical analytical reference value of 0.5-1.5 grams based on results from the literature (5,13,14).…”
Section: Study Participants and Collection Of Samplesmentioning
confidence: 96%
“…Therefore, an optimized sample collection process is needed, and a researcher must carefully and cautiously prepare the sample collection step, and the patient must be educated and trained if sample is being to be collected at home. Furthermore, steps like sample storage and transport to the laboratory must also be carefully planned and executed especially when longitudinal studies of the same patient or of the patients' groups are being performed, and especially in parts of the world where appropriate infrastructure is not always available [40][41][42][43][44][45].…”
Section: Sample Collectionmentioning
confidence: 99%